Broadband Internet and Attitudes Towards Migrants: Evidence from Spain - Marta Golin; Alessio Romarri (Institute of Labor Economics (IZA), 2022)
In this paper, we empirically evaluate the effect of exposure to broadband Internet on attitudes towards immigrants. We combine innovative survey data from Spain with information on the characteristics of the Spanish telephony infrastructure. To address the endogeneity of Internet availability, we exploit the fact that high-speed Internet in its early phases was supplied through the existing fixed telephone lines. We use landlines penetration as an instrument for broadband diffusion at the municipality level, and use data from both the pre- and post-Internet period to estimate a difference-in-difference instrumental variable model. We document a positive effect of broadband Internet penetration on attitudes towards immigrants at the municipality level. This result is particularly strong among young and urban individuals. Looking at mechanisms, we find that broadband Internet is associated with a better knowledge of (national) immigration dynamics and smaller concerns about the effects of migration on the labor market. Finally, using a combination of survey and electoral data, we find that broadband Internet penetration reduces political support for the Partido Popular, Spain's traditional right-wing party.
Keywords: D72; D83; J15; 330; internet; attitudes; immigration